2021
DOI: 10.1016/j.nuclphysa.2020.122077
|View full text |Cite
|
Sign up to set email alerts
|

Cluster structure of 20Ne: Evidence for D3h symmetry

Abstract: We study the cluster structure of 20 Ne and show that the available experimental data can be well described by a bi-pyramidal structure with D 3h symmetry. Strong evidence for the occurrence of this symmetry comes from the observation of all nine expected vibrational modes (3 singly degenerate and 3 doubly degenerate) and of six (singly degenerate) double vibrational modes. 20 Ne appears to be another example of the simplicity in complexity program, in which simple spectroscopic features arise out of a complex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…On the other hand, the g-factors of the sd -shell nuclei up to 29 Si are obtained from USDB interaction [65], and some disagreement with the experimental data is detected only for the (3/2) + 1 and (5/2) + 1 states of 21 Ne [57]. The discrepancy is slightly filled by the ab-initio in-medium similarity renormalization group (IM-SRG) approach, yielding g = −0.443 and −0.140 for the two states, respectively.…”
Section: N = Z + 1 Nucleimentioning
confidence: 95%
See 3 more Smart Citations
“…On the other hand, the g-factors of the sd -shell nuclei up to 29 Si are obtained from USDB interaction [65], and some disagreement with the experimental data is detected only for the (3/2) + 1 and (5/2) + 1 states of 21 Ne [57]. The discrepancy is slightly filled by the ab-initio in-medium similarity renormalization group (IM-SRG) approach, yielding g = −0.443 and −0.140 for the two states, respectively.…”
Section: N = Z + 1 Nucleimentioning
confidence: 95%
“…Nevertheless, for the lowest-energy states, SMbased approaches as the cluster-orbital shell model (COSM) [87] seem to provide a rather faithful description [88,89]. Moreover, a recent CSM analysis of the whole low-energy spectrum and the electromagnetic multipole transition probabilities of 21 Ne [42] suggests, that particle and hole neutron states can coexist with the underlying 20 Ne core, thus exciting the internal degrees of freedom of one of the α-particles. The comparison with the experimental energies turns out to be favourable for the model, except for the missing K P = 1/2 + band starting at 17.34 MeV [42].…”
Section: N = Z + 1 Nucleimentioning
confidence: 99%
See 2 more Smart Citations
“…By using the cranking covariant density functional theory (CDFT), the rod-shaped carbon isotopes at high spins were studied [48,50,51]. The studies based on the algebraic model [52] and the antisymmetrized molecular dynamics (AMD) model [53] suggested that the α clustering can appear in the lowlying states of 12 C and other light even-even nuclei [54][55][56]. In order to study how the nuclei cluster and how the clustering influences the nuclear properties, we need theories that can describe both the excited states and the ground state, and include as many shape degrees of freedom as possible.…”
Section: Introductionmentioning
confidence: 99%